Comparison of neuroprotective properties of the dipeptide mimetics of the 1st, 2nd and 4th loops of the brain-derived neurotrophic factor on the model oxidative stress in vitro - I. O. Logvinov; A. V. Tarasiuk; N. M. Sazonova; P. I. Antipov; T. A. Antipova; T. A. Gudasheva (LLC "Publisher OKI", 2019)
Resume. The purpose of this study was to compare neuroprotective properties of the dimeric dipeptide mimetics of the 1st, 2nd and 4th Loops of BDNF - GSB-214 (heptamethylenediamide bis-monosuccinyl-methionyl-serine), GTS-201 (hexamethylenediamide bis-hexanoyl-seryl-lysine) and GSB-106 (hexamethylenediamide bis-monosuccinyl-seryl-lysine) in the HT-22 hippocampal cells in conditions of oxidative stress. It has been established that the mimetic of the 4th loop of BDNF shows a neuroprotective effect in lower concentrations compared to mimetics based on the 1st and 2nd loops when applied 24 hours before and immediately after the damages.